Prevalence of hepatitis B among pregnant women assisted at the public maternity hospitals of São Luís, Maranhão, Brazil - Souza,Marinilde Teles (2012)
INTRODUCTION: Hepatitis B virus (HBV) infection is an important worldwide public health problem. In Brazil, the Ministry of Health estimates that 15% of the population has had contact with HBV, and that the mean rate of chronic carriers in Northeastern Brazil is around 0.5%. OBJECTIVE: The aim of this study was to assess the prevalence of HBV markers in pregnant women receiving prenatal care at the public maternity hospitals of São Luís. Methods: Demographical and epidemiological data were collected from 541 pregnant women according to the research protocol. Blood samples were collected, and the anti-HBc test was performed first. If positive, the sample was subsequently tested for HBsAg and anti-HBs. All HBsAg and/or anti-HBc positive samples were additionally tested for HBV-DNA. RESULTS: 40 (7.4%) pregnant women turned out positive for anti-HBc. Of those, five (0.9%) were HBsAg positive, four (0.7%) were anti-HBc positive with negative HBsAg and anti-HBs, and 31 (5.7%) were positive for anti-HBc and anti-HBs. Anti-HBc positivity was associated with family history of hepatitis and education level below 11 years of schooling. HBV-DNA was positive in only one HBsAg-positive sample. There was no HBV-DNA positivity among HBsAg negative samples. CONCLUSIONS: The prevalence of HBsAg in pregnant women in this study confirmed that São Luís is a low endemicity area. Occult hepatitis B was not detected in these samples.